Misrepresentation - Arowosaiye, Yusuf Ibrahim; Masum, Ahmad; Ali Mohamed, Ashgar Ali; Ahmad, Muhamad Hassan (CLJ Malaysia Sdn Bhd, 2024)
Misrepresentation is an untrue statement which the maker believes is true and without any intention of deceiving the misled party. In the case of fraud, on the other hand, the maker of the false statement or representation does not believe in the truth of the statement made and has the conceived intention to deceive the misled party. Although the two concepts are not the same by the above underpinning factor of intent to deceive or without intent to deceive, both result in the same effect with regards to the contract in question, as the consent of the other party is not freely given, being induced by fraud or misrepresentation. By virtue of the provision of s. 14 of the Contracts Act, the agreement is a contract voidable at the instance of the misled party whose consent was not freely obtained but with the influence of fraud or misrepresentation. It then means that the misled party has the option to affirm or repudiate the contract.